The Effect of Second-Language Proficiency on Second Language Reading Comprehension - Pohlmann, John T. (Per Linguam : A Journal of Language Learning, 1991)
Data from a first-language reading test, a second-language reading comprehension test with questions from different cognitive levels, and from the TOEFL were submitted to partial correlation analysis to detennine whether there was a significant effect of second-language proficiency on second-language reading comprehension when the influence of first-language reading comprehension was held constant. The results indicated that for factual and inference questions second-language reading comprehension may be more closely related to second-language proficiency than to first-language reading comprehension. The lack of a similar relationship for the generalization questions may be due to a substantial variation in the second-language readers' fonnal and content background knowledge which is necessary for the processing and comprehension of generalization questions. Data van 'n eerste taal-leestoets, 'n tweede taal-leesbegripstoets met vrae op verskillende kognitiewe vlakke en van die TO EFL is aan gedeeltelike korrelasie-ontleding onderworpe om vas te stel of daar 'n beduidende bei"nvloeding van tweede taal-vaardigheid op tweede taalleesbegrip was terwyl die invloed van eerste taal-leesbegrip konstant gebly het. Die resultate het aangedui dat wat feitelike en gevolgtrekkingsvrae betref, tweede taal-leesbegrip moontlik nader verwant is aan tweede taal-vaardigheid as aan eerste taal-leesbegrip. Die afwesigheid van 'n soortgelyke verhouding betreffende die veralgemeningsvrae is moontlik te IV)lte aan 'n aansienlike variasie in die tweede taal lesers se fonnele en inhoudelike agtergrondkennis wat nodig is vir die verwerking en begrip van veralgemeningsvrae.